Cintaikkiṉiya Cīrā - Mustapā, Maṇavai, 1935-; Cintaikkiṉiya (Mīrā Ḵapauṇṭēṣaṉ, 1978)
Study of Umarup Pulavar's Cīrāppurāṇam, an epic about Muhammad, the Prophet; articles presented at a seminar in 1976.